Road segment delineation using active testing principle and an edge-based post-processing strategy - Dal Poz, Aluir Porfirio [UNESP]; Silva, Marco Aurélio Oliveira da [UNESP] (My University, 2003)
This paper presents a semi-automated method for extracting road segments from medium-resolution images based on active testing and edge analysis. The method is based on two sequential and independent stages. Firstly, an active testing method is used to extract an approximated road centreline which is based on a sequential and local exploitation of the image. Secondly, an iterative strategy based on edge analysis and the approximated centreline is used to measure precisely the road centreline. Based on the results obtained using medium-resolution test images, the method seems to be very promising. In general, the method proved to be very accurate whenever the roads are characterized by two well-defined anti-parallel edges and robust even in the presence of larger obstacles such as trees and shadows.
Keywords: airborne sensing; image processing; remote sensing; road; satellite imagery; spatial resolution